A procedure for selective full length cDNA cloning of specific RNA species. - Schmid, A (1987)
A method allowing routine establishment of full length and functionally competent cDNA clones of particular mRNAs from small preparations of polyadenylated RNA is described. Pairs of synthetic primers are used for first and second strand synthesis. They include sequences complementary to the 3' terminal regions of the mRNAs and of the full length first cDNA strands, respectively and bear a few additional nucleotides at their 5' ends. After synthesis of both cDNA strands in one tube, they are precisely trimmed back with T4 DNA polymerase in presence of only two nucleoside triphosphates, to yield sticky ends fitting into a vector plasmid cleaved with two restriction endonucleases. The procedure was first applied to the simultaneous cloning of all five major measles virus (MV) mRNA species from a persistently infected cell line. Two thirds of all clones contained full length MV-specific cDNAs. Screening of less than 200 clones was sufficient to obtain several independent clones corresponding to each mRNA, except for gene F which was represented only once.